Indicators of ecosystem potential for pollination and honey production. (November 2018) - Affek, Andrzej Norbert
Highlights: Indicator-based assessment is linked to real regional data on wild bees and honey plants. Grassland, in contrast to other studies, has the highest potential to offer bee services. Distribution of potentials for bee services contrasts with many other ecosystem services. Major differences were noted among ecosystems that fall into the same CLC or MAES class. Abstract: The estimation of the value of nature in terms of benefits derived by humans is becoming increasingly popular in environmental assessments and spatial planning worldwide. In line with this approach, the value of any ecosystem can be determined on the basis of its potential (capacity), or the actual amount of goods and services delivered (flow). The aim of this work was to develop indicators of the potential of ecosystems to deliver services related specifically to bees, i.e. to pollination and honey production. A new operational definition of ecosystem potential dedicated to the evaluation of bee-related services was introduced and applied. Two ratio scales were constructed, showing the potential abundance of nesting wild bees (indicating pollination) and the availability of honey substrates (indicating honey production). The expert assessment carried out was closely linked to real regional data. Specific values were assigned to 29 types of ecosystem relevant to bees and identified in the lowland rural landscape of Central Europe. The original scales for the indicators were then classified into the 0–10 ecosystem capacity scale. A specific study area in north-eastern Poland (815 km 2 ) was chosen to show a possible spatial pattern for ecosystem potential in relation to the two bee-related services. Dry grassland and early successional pine forests were assigned highest values in terms of pollination potential, as well as cropland, young swamp pine forests and dry grassland in the case of honey production. In turn, mature alder and riparian forests, together with wetlands, ranked lowest for both bee services. This study confirmed that ecosystem capacities to deliver bee services tend to contrast greatly with potentials as regards many other ecosystem services (e.g. carbon sequestration or erosion control). This obviously complicates management policies and requires that the concept of trade-offs be embraced. The proposed indicators, as combined with detailed mapping of ecosystem capacities differ from pan-European modelling in being of value to particular stakeholders, and in support of decision-making processes regarding beekeeping, farming and nature conservation.